Internal fixation of acetabular fractures in an older population using the TIMI approach – Midterm results of a prospective study. Issue 4 (April 2017) - Aigner, Rene; Hellige, Ralf; Knippel, Sabine; Oberkircher, Ludwig; Ruchholtz, Steffen; Buecking, Benjamin
Abstract: Introduction: The incidence of geriatric acetabular fractures continues to increase due to demographic changes. In the elderly, anterior column fractures are common, and standard approaches are associated with a considerable risk for surgery-associated complications. Therefore, a minimally invasive approach was developed in our department. The aim of this study was to examine early and mid-term results regarding the use of this novel two-incision minimally invasive (TIMI) approach in patients aged over 55 years with acetabular fractures. Methods: From July 2007 to April 2014, 47 patients aged over 55 years were treated via the TIMI approach; these patients were included in the present prospective study. The patients' characteristics, data, and early phase of care were assessed during acute care. A radiological evaluation comprised pre- and postoperative CT scans and x-rays, including Judet views at follow-up. Follow-up examinations were performed after 6 and 24 months and comprised a clinical and radiological examination and an evaluation of hip function (Harris Hip Score) and health-related quality of life (EQ-5D). Results: The mean age of the patients was 74 ± 11 years, with a gender ratio of 35/12 (m/f). The average operation time was 93 ± 30 min, and perioperative blood loss amounted to 858 ± 463 ml. In total, five (11%) complications associated with the operative procedure occurred, and revision surgery was necessary in three patients. We observed no wound infections, abdominal wall hernias or cases of heterotopic ossification in our sample. The Harris Hip Score at six months after surgery was 81, and it slightly improved to 84 after 24 months. The mean EQ5D index was 0.91 at six months after surgery and 0.92 at 24 months after surgery. Conclusion: The TIMI approach represents a valuable alternative to the ilioinguinal and modified Stoppa approach for the treatment of acetabular fractures located in the anterior column, which are often observed in geriatric patients. Level of evidence: Therapeutic Level II (Prospective cohort study).